The Buffering Effect of Supervisor Support on the Relationship between Perceived Stress and Turnover Intention among Female Nurses in Saudi Arabia - Alshutwi, PhD, RN., Dr. Sitah (International Journal of Innovative Research in Medical Science, 2021)
Background: The shortage of registered nurses is a worldwide concern; with many countries struggling to maintain adequate numbers of nurses. Many factors that contribute to nursing shortage have been studied, but the influence of work–family conflict has received little attention. Work–family conflict has been linked to a number of work-related consequences, including turnover intention among employees. The aim of this study was to evaluate the influence of supervisory support behaviours on the relationship among work–family conflict, Stress, and turnover intention. Sample: 113 nurses. Result: A significant positive correlation was found between work–family conflict and turnover intention. A negative correlation was found between supervisory support behaviours and turnover intention. Both work–family conflict and stress were associated with turnover intention; however, these associations were buffered (weaken), when nurses perceived higher supervisory support behaviours. Conclusion Supervisory support behaviours could be the tool to help married, female nurses play their professional role without compromising their family responsibilities. Nurses’ turnover is a complex issue that may require multiple prevention strategies; however, enhancing family supportive supervisor behaviors could be a key resource for maintaining a positive workplace environment and reducing turnover intention.